Elementary Particles are not Substances - Verrill, Robert (Proceedings of the American Catholic Philosophical Association, 2017)
The doctrine of the salvation of souls is obviously central to our Christian faith. Yet one of the challenges of communicating this truth is that many people have ontological commitments that don't even allow for the existence of souls. Therefore, a philosophical understanding of physical reality which is compatible with a Christian understanding of the human person is especially important if we are to preach the Gospel effectively in the modern age. Like many Christian philosophers, I believe that St. Thomas Aquinas provides us with such a philosophical understanding of physical reality. Nevertheless, we need to be careful in how we map Aquinas's philosophical concepts onto physical phenomena. It is with this concern in mind that I will argue that elementary particles are not substances.